Airline Route Structure Competition and Network Policy - Hugo Emilo Silva; Erik T. Verhoef; Vincent van den Berg (Tinbergen Institute, 2013)
This paper studies whether a regulator needs to correct the route structure choice by carriers with market power in the presence of congestion externalities, in addition to correct their pricing. We account for passenger benefits from increased frequency, passenger connecting costs, airline endogenous hub location and route structure strategic competition. We find that, for some parameters, an instrument directly aimed at regulating route structure choice may be needed to maximize welfare, in addition to per-passenger and per-flight tolls designed to correct output inefficiencies. This holds true when the regulator is constrained to set non-negative tolls, but also for the case of unconstrained tolling.
Keywords: H2; L13; L93; R4; 330; Route structure competition; Aviation policy; Hub-and-spoke networks; Fully-connected networks